Serum bilirubin predicts long-term clinical outcomes in patients with cardiac syndrome X. Issue 15 (16th July 2010) - Huang, Shao-Sung; Huang, Po-Hsun; Leu, Hsin-Bang; Wu, Tao-Cheng; Lin, Shing-Jong; Chen, Jaw-Wen
Abstract : Background: Increased oxidative stress and vascular inflammation have been demonstrated in patients with cardiac syndrome X (CSX). Bilirubin, once considered simply the metabolic end product of haem degradation, has emerged as a potential endogenous inhibitor of atherosclerosis. This study was conducted to evaluate the prognostic role of serum bilirubin in disease progression and clinical outcome in patients with CSX. Methods: A total of 108 consecutive CSX patients were enrolled. Serum bilirubin levels were examined from blood samples collected before coronary angiography. All patients were prospectively followed up for 5 years for the composite end point of total adverse events including death and non-fatal cardiovascular events (non-fatal myocardial infarction, ischaemic stroke, rehospitalisation for unstable angina, and coronary revascularisation). Results: There were 20 adverse events, including five deaths, five ischaemic strokes and 10 rehospitalisations for unstable angina during follow-up. Patients with adverse events had lower baseline serum bilirubin levels (p<0.001). All patients were stratified into high-bilirubin, normal-bilirubin and low-bilirubin groups. The patients in the high-bilirubin group had the lowest incidence of total adverse events (p=0.008) and non-fatal cardiovascular events (p=0.008). In a multivariate Cox regression analysis, serum bilirubin, in addition to age and basal superoxide generation of circulating mononuclear cells, was also an independent predictor of total adverse events (HR 0.002; 95% CI 0.000 to 0.520; p=0.028). Conclusions: In patients with CSX, baseline serum bilirubin level was associated with long-term outcomes. Serum bilirubin could be a predictive and protective biomarker for disease progression and the development of cardiovascular events in CSX patients.